Representações discentes sobre a inserção e permanência de homens no curso de Pedagogia da UFLA: entre desafios, resistências e rotas alternativas - Resende, Tatiane Patrícia (2018)
The present research aims to identify the representations of students of the course of Pedagogy, face-to-face, of the Federal University of Lavras (UFLA) located in Minas Gerais, about the insertion and permanence of men in undergraduate courses, taking into consideration that Pedagogy is a women's reserve space and the process of feminization of the teaching profession. It starts from the understanding of the reasons that lead to social representation in the course of Pedagogy, built historically and culturally, that the woman is educator by nature, which ends up denying the possibilities and potentialities of the male pedagogue. Therefore, one has as a question-research problem what are the representations of students of the Pedagogy on the insertion and permanence of men in the course. This research stems from the understanding of the university space as an environment where unequal gender relations are perpetuated, but at the same time, conducive to problematization and deconstruction. Under a qualitative approach the information obtained through narrative interviews with a semi-structured script with students of the Pedagogy course is analyzed. The interpretation of this empirical material was based on Foucauld's perspective of problematization and Discourse Analysis, anchoring myself in gender studies, feminist studies, and poststructuralist studies for a broader and more reasoned reflection. For that, it brings theoretical considerations about the concepts of identity and gender, establishing the interweaving of these with the processes of constitution of the teaching identities, in the context of teaching under construction. It is hoped that this research contributed to the deconstruction of stereotypes and hegemonic representations about teaching, as well as to highlight the efforts of those who symbolize the resistance in this space / formative time and, in order to contribute socially and give feedback to the course , we set some measures for the management of the Pedagogy course so that the problem of the insertion of men is problematized in the formation and in the curricular matrix, making possible the reflection on the historical, social and cultural construction of gender differences and inequalities in the performance of pedagogues and means that facilitate the inclusion of all in the various training activities.